ACADEMIC COLLABORATIONS IN THE AMERICAS: SOME REFLECTIONS ON THE POLITICAL ECONOMY OF LEGAL KNOWLEDGE - Bonilla Maldonado, Daniel; Crawford, Colin (Revista Eletrônica do Curso de Direito da UFSM, 2017)
The article proceeds in three parts. The first, the articles’ analytical heart, considers the political economy of legal knowledge. It describes briefly the free market of legal ideas and the colonial model for the production of legal knowledge. It illustrates how these two models work using examples from our “South-North Partnerships” (SNP), that is, our collaborative practices in the creation of legal thought as they play out in the legal academies of the global North and South. The second part is both descriptive and reflective, focusing on four different SNP examples that illustrate challenges in the creation of truly collaborative legal knowledge production processes. It identifies common challenges in these endeavors, from surmounting basic organizational issues such as language barriers to jostling with fundamentals like conflicting academic calendars. Most importantly, the second part indicates how the dynamics of the political economy of legal knowledge played out in the SNPs described. It also highlights possible ways to equalize these relationships and activities, with an end to creating SNPs focused on truly collaborative legal knowledge production. The third part offers conclusions and recommendations.